Desenvolvimento de gel contendo extrato hidroetanólico de Varronia curassavica Jacq (erva-baleeira) - Freitas, Yasmim Taranto de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O Brasil, por sua vasta biodiversidade, possui grande potencial para a implantação da Fitoterapia como recurso terapêutico no Sistema Único de Saúde (SUS), baseado na flora medicinal brasileira. Assim, vários projetos de Farmácias Vivas vêm sendo implantados em diversos municípios brasileiros. Estas visam toda a cadeia produtiva de plantas medicinais e fitoterápicos e, também, sua distribuição via prescrição médica no SUS. Varronia curassavica Jacq, conhecida popularmente como ervabaleeira, é muito utilizada por comunidades, a partir de preparações tradicionais, devido, principalmente, à sua ação anti-inflamatória. Várias são as formas farmacêuticas utilizadas em projetos de Farmácias Vivas, dentre elas géis. O objetivo do presente trabalho foi desenvolver um gel contendo o extrato hidroetanólico 70% preparado a partir das folhas de erva-baleeira, assim como realizar um estudo de estabilidade acelerada, avaliando os seguintes parâmetros: cor, odor, pH e viscosidade, durante 120 dias, submetidos a 4 condições: estufa, geladeira, luz indireta e ambiente. Os resultados obtidos demonstraram que não houve grandes alterações de cor, odor, pH e viscosidade das amostras de gel, analisadas nas diferentes condições, indicando que nas 4 condições as amostas se mantiveram estáveis durante o período de teste. Com isso, o estudo comprova a estabilidade da formulação desenvolvida, fornecendo o gel como uma nova forma de administração, que pode estar disponível à população, a partir das Farmácias Vivas no SUS, além de infusão e creme, já disponíveis, trazendo a valorização da flora brasileira e do saber tradicional. Brazil, due to its vast biodiversity, has great potential for the implementation of Phytotherapy as a therapeutic resource in the Unified Health System (SUS), based on the Brazilian medicinal flora. Thus, several projects of Farmácias Vivas have been implemented in several Brazilian municipalities. These are aimed at the entire production chain of medicinal plants and herbal medicines, as well as their distribution via medical prescription in the SUS. Varronia curassavica Jacq, popularly known as “erva-baleeira”, is widely used by communities based on traditional preparations, mainly due to its anti-inflammatory action. There are several pharmaceutical forms used in Living Pharmacies projects, among them gels. The objective of the present work was to develop a gel containing the 70% hydroethanolic extract prepared from the leaves of “erva-baleeira”, as well as to carry out an accelerated stability study, evaluating the following parameters: color, odor, pH and viscosity, during 120 days , arranged in 4 conditions: greenhouse, refrigerator, indirect light and environment. The results showed that there were no major changes in color, odor, pH and viscosity of the gel samples analyzed under different conditions; indicating that they remained stable during the test period. With this, the study proves the stability of the developed formulation, providing the gel as a new form of administration, which may be available to the population from Farmácias Vivas in SUS, in addition to infusion and cream, bringing the appreciation of the Brazilian flora and knowledge traditional.

Brazil, due to its vast biodiversity, has great potential for the implementation of Phytotherapy as a therapeutic resource in the Unified Health System (SUS), based on the Brazilian medicinal flora. Thus, several projects of Farmácias Vivas have been implemented in several Brazilian municipalities. These are aimed at the entire production chain of medicinal plants and herbal medicines, as well as their distribution via medical prescription in the SUS. Varronia curassavica Jacq, popularly known as “erva-baleeira”, is widely used by communities based on traditional preparations, mainly due to its anti-inflammatory action. There are several pharmaceutical forms used in Living Pharmacies projects, among them gels. The objective of the present work was to develop a gel containing the 70% hydroethanolic extract prepared from the leaves of “erva-baleeira”, as well as to carry out an accelerated stability study, evaluating the following parameters: color, odor, pH and viscosity, during 120 days , arranged in 4 conditions: greenhouse, refrigerator, indirect light and environment. The results showed that there were no major changes in color, odor, pH and viscosity of the gel samples analyzed under different conditions; indicating that they remained stable during the test period. With this, the study proves the stability of the developed formulation, providing the gel as a new form of administration, which may be available to the population from Farmácias Vivas in SUS, in addition to infusion and cream, bringing the appreciation of the Brazilian flora and knowledge traditional.
Development of gel containing hydroethanolic extract of Varronia curassavica Jacq (erva-baleeira)
Keywords: Varronia Curassavica Jacq.; erva-baleeira.; Gel.; Farmácia Viva.; Desenvolvimento de formulação.; Estabilidade acelerada.